(untitled) (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
This article discusses the meaning of Lombok in contemporary Indonesian novels with a focus on the novel Sanggarguri. The novel discusses the concept of heterodox teachers in Islam. The novel is presented in the context of opposing orthodox Islamic discourse on the concept of ‘guru’. To discover the concept of ‘guru’ in Sanggarguri, this article applies representation theory with a constructionist approach. With that approach, the novel is assumed not to be a presentation about Lombok, but a representation of Lombok. Data were language, both word and paragraph, both in narrative and metaphorical form. Data analysis was performed using semiotic and discourse methods. The results of the analysis show that the novel Sanggarguri conceptualizes Lombok into a traditional discourse by using the names of flowers (kembang) as stages that exist in Sasak Islamic spirituality. The stages from gadung flower to ‘Sanggar Guri teacher’, a wisdom expert teacher, reveal that the concept of a teacher in heterodox Sasak Islam is open to anyone. It belongs to anyone and anywhere. The concept is different from the concept of ‘guru’ in orthodox Islam promoted by ‘tuan guru’, whose knowledge is connected to Haramain. Therefore, only a few people can become ‘tuan guru’. The discourse of ‘guru’ in Sanggarguri is against the discourse of ‘tuan guru’ on the meaning of ‘guru’.